How Servant Leadership Affect the Organizational Trust with Mediating Role of Technological Innovation? - Hanif, Muhammad Imran; Baloch, Zarbakht; Baig, Salman (International Review of Management and Marketing, 2020)
The main objective of this paper is to investigate how servant leadership affects organizational trust with the mediating role of technological innovation. In this paper we discussed that technological innovation played a vigorous role in all types of organizations and leadership having the qualities of a servant also played a vital role in achieving the trust because trust is the most crucial element for an organization. A descriptive cross-sectional survey design was used in conducting the study. The data for this study was taken from public and private organizations that are engaged in providing products and services to their customers. 370 questionnaires were distributed among different respondents. 310 useable respondents were selected and the questionnaire includes close-ended questions related to leaders, organization and technological factors. Cross-sectional quantitative research design was adopted. The purposive sampling technique was used for this study. Findings of this study shows that the mediating the variable "technological innovation" strengthens the affiliation among autonomous "servant leadership" and "organizational trust" dedicated to their work, and this is so beneficial to the organisation.Implications based on these finding, the study enticement the attention of mangers concerning the role of Servant Leadership, trust in the organization and flourishing the employee creativity with the help of technological innovation. This study suggests that servant leadership is an important factor that influences organizational trust because trust is the most crucial component and technological innovation with servant leadership qualities emerged to achieve trust. Keywords: Servant Leadership, Technological Innovation, Organizational Trust. JEL Classifications: M1, 03, M0 DOI: https://doi.org/10.32479/irmm.10183